2017
DOI: 10.24843/blje.2017.v17.i02.p04
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kualitas Air Irigasi Dumoga Di Kabupaten Bolaang Mongondow Provinsi Sulawesi Utara

Abstract: Water Irrigation a very important and is one key to the success of the increased production of rice plants in the paddy field.  The aim of this study was to assess the water quality Irrigation Dumoga at Kabupaten Bolaang Mongondow Province Sulawesi Utara. Data collected by observation of agriculture activity and determination of sampling by using composite sampling method at canal Irrigation Dumoga. Measurement in situ pH, and temperatur.  Analysis concentration total dissolved solid (TDS), total suspended sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The measurements of the Sodium Adsorption Ratio (SAR) at the two research locations showed different results with SAR values of 7.975 for Lake Perintis and 11.214 for Lake Limboto. A study conducted by Wantasen & Luntungan (2017) in Lake Dumoga found a score of 8.89, classified in the very good category and tending to be the same as that carried out in Lake Perintis and Lake Limboto. Based on the Sodium Adsorption Ratio, both research locations are included in the class suitable for plants.…”
Section: Classification Of Irrigation Water Based On Sodium Adsorptio...mentioning
confidence: 70%
“…The measurements of the Sodium Adsorption Ratio (SAR) at the two research locations showed different results with SAR values of 7.975 for Lake Perintis and 11.214 for Lake Limboto. A study conducted by Wantasen & Luntungan (2017) in Lake Dumoga found a score of 8.89, classified in the very good category and tending to be the same as that carried out in Lake Perintis and Lake Limboto. Based on the Sodium Adsorption Ratio, both research locations are included in the class suitable for plants.…”
Section: Classification Of Irrigation Water Based On Sodium Adsorptio...mentioning
confidence: 70%
“…Nitrite is an intermediate product performed by bacteria in the nitrification process performed by Nitrosomonas bacteria by remodeling ammonia into nitrites. Nitrosomonas bacteria carry out the oxidation of ammonia into nitrites in the process of nitrification, and Nitrobacter bacteria carry out the oxidation of nitrites into nitrates in aerobic conditions [14]. Nitrite is one form of inorganic nitrogen in the water, the nitrite content in catfish culture is not more than 1.0 mg/l [11] The process of converting nitrites into nitrates is carried out by Nitrobacter bacteria affected by oxygen.…”
Section: Figure 2 Graph Of Nitrite Fluctuationsmentioning
confidence: 99%
“…The nitrate content in the maintenance medium added with probiotics with the best dosage is 0.023-3.52 mg/L [9]. Nitrate (NO3) is a nutrient that, at excessive levels, can cause a decrease in the water quality of a body of water that eventually causes water pollution and results in eutrophication [14]. Water quality also affects the performance of bacteria in the nitrification process to remodel ammonia into nitrates.…”
Section: Figure 3 Graph Of Nitrate Fluctuationmentioning
confidence: 99%